Unraveling the occupational exposure to mycotoxins in a waste management setting: results from a case study in Norway - Martins, Carla (2025)
Introduction: Waste management represents an occupational setting where fungi are significant contaminants. This study aimed to assess the exposure of waste workers to mycotoxins through a human biomonitoring study. Methods: Thirty-three workers and 19 controls provided spot urine samples to determine 10 mycotoxins’ urinary biomarkers using liquid chromatography coupled with mass spectrometry. Risk characterization was performed using hazard quotient and margin of exposure assessments. Results: The results indicated that workers were exposed to six out of the 10 mycotoxins tested, with the following detection rates: deoxynivalenol (91%, 30/33), ochratoxin A (33%, 11/33), zearalenone (17%, 5/33), α-zearalenol (12%, 4/33), β-zearalenol (12%, 4/33), and HT-2 toxin (3%, 1/33). Within controls and outwith controls, were exposed to 5/10 and 2/10 mycotoxins, respectively. All participants exhibited hazard quotients for deoxynivalenol and zearalenone below one, indicating that the exposure is unlikely to pose a health risk. However, when considering the margin of exposure determined for ochratoxin A, 18% of the total participants presented results below 200 for non-neoplastic effects, and 100% of the total participants presented values below 10,000 for neoplastic effects, suggesting potential health concerns that require further assessment. Discussion: This study highlights the need for future research on occupational exposure to mycotoxins in waste management settings.